Utilizing Digital Game Based Learning to Enhance English Grammar Mastery Learning for the Third Year Students - Firdaus; Sunubi, Abdul Haris; Ambo Dalle; Arqam; Mujahidah (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2025)
This research aims to examine the effectiveness of Digital Game-Based Learning (DGBL) in improving the English grammar mastery of third-year students. The study also investigates student responses and engagement in the learning process. This research used a Classroom Action Research (CAR) design conducted in two cycles, involving 25 third-year students. The learning process utilized digital platforms such as Duolingo, Baamboozle, and Blooket as interactive grammar learning media. Data were collected through grammar tests, observation sheets, and field documentation. The results showed a significant improvement in students’ grammar mastery, with the average score increasing from 58.52% in Cycle I to 91.20% in Cycle II. In addition, students demonstrated very positive responses and increased engagement during the DGBL activities. The learning atmosphere became more dynamic, and students were more motivated to participate actively in class. The study concludes that Digital Game-Based Learning not only enhances grammar skills but also promotes positive attitudes and high engagement among students in a pesantren context.